HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU SISWA SMP-SMA X TANGERANG TERHADAP ROKOK SEBAGAI FAKTOR RISIKO PENYEBAB KANKER PARU - Angeline, Reni; Wijaya, Hertiawan; Ruchika, Ruchika; Christina, Shintia (Universitas Kristen Krida Wacana, 2024)
Lung cancer is the first cancer for men and the third for women based on cancer globally. Based on RISKESDAS, there is an increase in the prevalence of smokers every year in junior high and high school. This is because teenagers think smoking makes it easier for them to socialize. The purpose of this study was to determine the relationship between knowledge and attitudes towards the behavior of students of SMP and SMA X Tangerang towards smoking as a risk factor for lung cancer. This type of research uses analytic methods with a cross sectional approach. The sample used was 88 respondents with a simple random sampling technique. Data collection using a questionnaire and data analysis using Spearman. The results showed that there was a relationship between the level of knowledge and behavior with a value of p = 0.012 (p = <0.05). Likewise the relationship between attitude and behavior, there is a significant relationship with a value of p = 0.000 (p = <0.05). It was concluded that there was a significant relationship between knowledge and attitudes towards the behavior of students of SMP and SMA X Tangerang towards smoking as a risk factor for lung cancer.